Space charge phenomena on low-density poly ethylene film breakdown under heavy water absorption - Eka Putra Waldi; Rudy Fernandez; Yoshinobu Murakami; Naohiro Hozumi; Masayuki Nagao (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The effect of dry and heavy water absorption on the electrical breakdown of low-density poly ethylene film was investigated. The temperature rise of the sample was observed by thermograph until the electrical breakdown using    direct current ramp voltage. The conduction current of low-density poly ethylene film was also measured, and the result was then correlated with thermograph measurement. Meanwhile, the space charge distribution in asample was measured by the pulse electro-acoustic method. From the thermograph, the result can be seen that under the heavy water absorption, the sample was more dissipated than the dry condition. Then, the breakdown occurs at the lower value of the voltage application, but the higher conduction current. Furthermore, the pulse electric acoustic show that increases the charge injection to the sample in the heavy water absorption. Increased space charges associated with an increase in the current conduction and the formation of heating, which results in a thermal breakdown.